A long and unfinished path towards substantial equality and the need for a gender approach in public policies - Veliz Mayta, Gaudy Yely (2020)
Being that incursion of women into the labor market and education has led to changes, these do not translate into better conditions; Therefore, the need for a gender approach that allows the design of inclusive social policies that involve men as part of the problem. Thus, in the first order the history regarding the conquest of women’s rights is addressed, which unfortunately have  been more formal than substantial. Second, it addresses how gender stereotypes have perpetuated situations of inequity, hence the need for a gender approach as an instrument of analysis. Third, the need for social public policies with a gender approach that allow redefining spaces, greater equity, equality, substances that allow the enjoyment of women’s rights and greater participation of women in decision-making.